Aligning Inventory Accounting In Uzbekistan With International Standards (The Peerian Journal, 2024)
This article presents an overview of research on harmonizing inventory accounting with international financial reporting standards, based on the measures implemented in recent years to align the existing accounting and financial reporting system in Uzbekistan with International Financial Reporting Standards (IFRS). The study focuses on the efforts to bring the accounting of inventories in line with international standards within the framework of these broader initiatives. Recognition, valuation, and accounting of inventories. Scientific proposals and practical recommendations have been formulated based on the experience of foreign countries regarding the methodology for determining their cost.